International Law Enforcement Observer XIV. (Academic Journal of Internal Affairs, 2024)
Aim: Despite the fact that this time, the Observer provides insight into a wide range of topics in the international law enforcement literature – from counter-terrorism to football security – the editorial purpose that influenced the selection is still recognisable. The aim is to focus readers’ interest on methods that focus on facts and require publicity. Examples will be given that demonstrate that unjustified secrecy can be an obstacle not only to scientific research but also to effective professional work.Methodology: Tamás Drusza’s review shows that in the United Kingdom, a tactic of combining intelligence and criminal investigation is used to counter terrorism effectively, which also means that the flow of information between organisations is a critical point in the system's operation. Secrecy between authorities can lead to inefficiency. ‘The drawbacks of applying the principle of restricting the transfer of information have been confirmed by a survey of Europol staff. The general view is that proactively sharing information is as important as obtaining it.’ Of course, in order for such a counterproductive application of the principle of confidentiality to come to light, it was necessary for police academics to carry out the necessary research in a sensitive area of service and then publish the results in a way that would allow even Hungarian colleagues interested in the subject to be informed by means of a review.Findings: Beyond the threat of terror, all forms of violent radicalism in the broader sense need to be countered by social cohesion, as András Hunor Lehel illustrates with the Swedish example. ‘According to a 2016 report by the Swedish Security Service, approximately 300 people have left Sweden to join various violent Islamist groups abroad and fight alongside their organisations. Many of these men have returned to Sweden and represent a potential threat to the community.’ The study concludes that local authorities play a key role in detecting and preventing radicalisation, alongside central government. It is no coincidence that resilience has emerged as a key concept. Swedish municipalities are expected to develop plans that include measures to increase resilience at local and community level.Andrea Mészáros gives an insight into research conducted at the Tempe Police Department in Arizona. Here, they sought to understand how measures were affected by the pandemic in March 2020, and then by the national outcry over the death of George Floyd, a victim of police violence. The study analysed 474 measures, selected at random and all of which were recorded on body camera. Researchers said a review of the body-worn camera footage highlighted that despite the extreme circumstances, police officers handled encounters with citizens in a professional manner.Tamás Pressburger reports on new methods of policing football matches. The experience in England suggests that police officers responsible for the security of football grounds have successfully improved the effectiveness of their work through a change of approach, with sufficient training and practical experience. Police officers also need to work closely with the cultural and emotional dynamics of football fans, and need empathic skills to intervene effectively and constructively in escalating situations.Value: The reviews presented a number of solutions that have found new ways to challenge the traditional approach to policing. These include replacing the myth of secrecy with openness that emphasises cooperation, consensus based on empathy rather than confrontation, resilience that leads to the resolution of the trauma that accompanies violence, and the dissolution of centralisation with the principle of self-government.
Keywords: counterterrorism; radicalisation; resilience; body camera